1989
DOI: 10.1002/aja.1001840202
|View full text |Cite
|
Sign up to set email alerts
|

Normal stages of cardiac organogenesis in the mouse: I. Development of the external shape of the heart

Abstract: Normal development of the mouse embryonic heart was studied at the organ level using microdissection and scanning electron microscopy (SEM). Altogether 225 embryos, sampled at 8-hour intervals between 11ed (ed = embryonic day; day of vaginal plug = 1ed) and 15ed were collected. Their hearts were fixed by high flow-low pressure perfusion, microdissected, and observed in SEM. Standardized frontal, right profile, and left profile SEM micrographs were obtained and analyzed. The main purpose of this study was to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…These transitional zones are detected in the same positions as those where we observed the epicardial rings. The external shape of the embryonic mouse heart develops differently from that of the chick (Vuillemin and Pexieder 1989). We speculate that the spreading epicardial cells have more affinity for these intersegmental grooves than for the myocardium of the cardiac segments.…”
Section: Discussionmentioning
confidence: 85%
“…These transitional zones are detected in the same positions as those where we observed the epicardial rings. The external shape of the embryonic mouse heart develops differently from that of the chick (Vuillemin and Pexieder 1989). We speculate that the spreading epicardial cells have more affinity for these intersegmental grooves than for the myocardium of the cardiac segments.…”
Section: Discussionmentioning
confidence: 85%
“…In a normal E8.5 embryo, the heart tube begins to bend with only the primitive ventricle discernible (Vuillemin and Pexieder, 1989). After E8.5 embryos were cultured for 48 hr, we observed that they developed into E9.5-like embryos (n ϭ 15).…”
Section: Effects Of Rock Inhibition On Cardiac Morphogenesismentioning
confidence: 82%
“…To further investigate the effects of ROCK inhibition in cardiac chamber development, we cultured E9.5 embryos, in which the primitive atrium, ventricle, and conotruncus have already formed (Vuillemin and Pexieder, 1989). After 48 hr of culture, the E9.5 control embryos developed into E10.5-like embryos (n ϭ 12).…”
Section: Effects Of Rock Inhibition On Cardiac Morphogenesismentioning
confidence: 99%
“…In the mouse, the left ventricle and right ventricle are discernible at E9.5 and E11.5, respectively (Vuillemin and Pexieder, 1989a). From E12.5 to E13.5, the right ventricle grows larger than the left ventricle, and this relationship persists throughout embryonic development (Vuillemin and Pexieder, 1989a).…”
Section: Discussionmentioning
confidence: 98%